Innovative Approaches in Developing an Animal Model for Gonococcal Conjunctivitis: A Preliminary Stud - Aldy, Fithria; Zaitun Hasibuan, Poppy Anjelisa; Dewi Sari, Masitha; Mahmud Amin, Mustafa; Indriaswati, Luki; Pardianto, Gede; Sari Siregar, Dewi Indah; Ilmiati Fujiati, Isti (Journal of Neonatal Surgery, 2025)
Neisseria gonorrhoeae, the causative agent of gonorrhoea, is a major public health concern due to its widespread prevalence and rising antibiotic resistance. In addition to genital infections, N. gonorrhoeae can cause gonococcal conjunctivitis, an ocular infection that can lead to severe complications such as blindness. To better understand the pathogenesis of gonococcal conjunctivitis and investigate potential therapeutic strategies, this study aimed to establish a reliable animal model using the Wistar rat (Rattus norvegicus). Six rats were divided into six groups, each receiving six doses of N. gonorrhoeae (1.5 × 10⁶ CFU/mL) applied to the conjunctiva at 10-minute intervals. The rats were monitored for bacterial colonization at four time points: Days 1, 3, 5, and 7. Bacterial load was assessed using colony-forming unit (CFU) counts on Thayer-Martin agar, and molecular confirmation was performed via polymerase chain reaction (PCR) targeting N. gonorrhoeae DNA. Gram staining was also performed to verify bacterial morphology. Bacterial colonization progressed significantly over time, peaking on Day 5, with some rats exhibiting bacterial clearance by Day 7, while others showed persistent colonization. These results highlight the variability in host immune responses and the potential for chronic infection. The Wistar rat model offers valuable insights into the dynamics of N. gonorrhoeae infections in ocular tissues and serves as a platform for future studies on therapeutic and preventive interventions.